Marginalised women’s voices in the Indian environmental justice movement: stories from a Himalayan community - Kalyanwala, Kayonaaz (Frontiers in Communication, 2025)
Alternative media is increasingly a strategic tool in environmental justice movements. One area that remains especially understudied is how marginalised women, specifically, indigenous and Dalit women, use alternative media in India to put forward their own perspectives on environmental justice, sustainable development, and climate change. This paper contributes by bringing together studies of digital media and environmental justice using their shared concepts of reclaiming power, justice, and citizenship. The research provides a feminist perspective on whose knowledge is valued; who creates knowledge; and whether production of alternative knowledge challenges dominant discourses in media and policy about environmental justice. The paper shares select findings about research on the communicative practice of an Indian grassroots women’s collective which has recently started using digital media to share rural perspectives on environmental justice. The paper foregrounds an Ecolinguistic analysis of the media produced by these women, bolstered by findings from participatory workshops and interviews which point to the production context as well as power asymmetries women face. Analysing the women’s narratives, we see that they document traditional practices of farming, seed diversity, accessing small forest produce, and heritage skills such as weaving. The analysis reveals how women use their stories to make women’s roles visible in farming, local crafts, rituals and conservation. They also use the stories to position themselves as experts and memory keepers of traditional ways of life. Further, they produce discourses about development which value a symbiotic relationship between humans and nature; where culture, spirituality and nature are enmeshed, and which is critical of a neo-liberal development agenda.